NUMERICAL HEAT TRANSFER ON JET IMPINGEMENT COOLING OF CHIPS WITH SQUARE HOLES - Attiq Ur Rehman; Muhammad Shahid Farooq; Khawar Abbas; Hassaan Ahmad; Dong Yang (Spectrum of Engineering Sciences, 2025)
This work presents a three dimensional (3-D) incompressible flow numerical simulation in order to investigate the natural convection heat transfer and laminar flow through jet square holes, Enhance Heat transfer between solid material and fluid was considered and under investigate in the numerical analysis. This heat transfer and fluid flow phenomena numerically analyze assume continuity equation, momentum equation and energy equation and adopt thermal equilibrium model by using commercial CFD software ANSYS Fluent software 19.0. Boundary condition in this numerical analysis generalized through SIMPLE algorithm scheme. Three-dimensional incompressible flow simulation of heat transfer and laminar flow represents the results of Nusselt number (Nu), pressure drop (ΔP). A numerical solution using governing equation, continuity equation, momentum equation and energy equation of partial differential equation is obtained using SIMPLE algorithm scheme and for pressure, energy and momentum used second order & second order upwind scheme for gradient used Least Square cell based. Titanium electrode used as heat source Fluid as HFE7000 is used as coolant flow impinge on the titanium electrode (heat source). Initialization the problem used Hybrid Initialization solution method. The result obtain are discussed in term of Nusselt number, pressure drop with different jet arrangement pattern at 45 (L/s) volume flow rate.